Garantizar la discreción del banco central en la emisión de préstamos de estabilización en tiempos de la pandemia del Covid-19 - Oleg Podtserkovnyi; Kristina Vozniakovska (Universidad Hemisferios, 2020)
Restrictive measures imposed by governments around the world to counter the Covid-19 pandemic undoubtedly have a negative impact on the economy. One of the instruments of the state, which makes it possible to save entire sectors of the economy, including the banking sector, from bankruptcy, is the stabilization loans of the central bank. Accordingly, the analysis of the discretionary powers of central banks and their governing bodies in issuing stabilization loans to overcome the economic consequences of the Covid-19 pandemic is relevant and timely. The authors used different scientific methods, such as the dialectical method, the method of comparison, the method of elementary-theoretical analysis and synthesis, the hermeneutic and the forecasting analysis. As a result of the study, the authors substantiated a definition of the powers of the governing body of the central bank in making decisions on the provision of stabilization loans to banks, as part of the function of the central bank to maintain the stability of the national currency and the indicative regulation of banks. The authors concluded that there is a need for an expanded approach to the limits of the discretion of the central bank, on the basis of harmonization of economic purpose of decisions on the issuance of stabilization loans to banks, in accordance with the constitution and the laws.